Las Experiencias Con Relación a la Práctica de la Danza y su Influencia en el Autoconcepto de un grupo de Adolescentes Entre Los 14 a 17 Años de Edad de la Academia De Danza Firework House Ubicada en la Localidad Ciudad Bolívar, Bogotá D.C (2021)
The present research was carried out with the objective of understanding the experiences of dance practice and its influence on self-concept in a group of adolescents between 14 and 17 years of age from the Firework House dance academy located in the town of Ciudad Bolívar. Bogotá DC It was developed from the qualitative section of the research, with an exploratory scope and with a phenomenological methodological design. The instrument of the phenomenological interview was used, which allowed us to understand the experiences of the participants with respect to the practice of dance and discover the elements in common that were closely linked to self-concept